MO125NON-AMYLOID TYPE OF MONOCLONAL GAMMOPATHY OF RENAL SIGNIFICANCE: CLINICAL AND MORPHOLOGICAL SPECTRUM AND LONG-TERM RENAL OUTCOME*. (29th May 2021) - Khrabrova, Maria; Smirnov, Alexei; Dobronravov, Vladimir; Kudjasheva, Olga
Abstract: Background and Aims: Monoclonal gammopathy of renal significance (MGRS) is a clinically and morphologically diverse kidney damage caused by monoclonal immunoglobulin (IG) produced by a "small" B-cell clone. Non-amyloid type of MGRS is considered to be rare but associated with poor kidney outcome (KO). The analysis of the prevalence, clinical and morphological spectrum and long-term renal prognosis in different degrees of hematological response (HR) in patients with non-amyloid type of MGRS became the goal of this study. Method: In this one-center prospective study performed from 01.01.2011 till 01.03.2020 patients with MGRS were enrolled. Criteria of MGRS were following: i) morphologically verified monoclonal IG related kidney damage and ii) an aberrant clone in the bone marrow and/or the level of serum/urine paraprotein not met the hematological criteria for treatment initiation. Cases of renal AL-amyloidosis were excluded. The morphological spectrum of non-amyloid MGRS, treatment, hematological and renal responses (RR) were analyzed. HR was assessed depending on the type of monoclonal IG according to the accepted criteria. The presence of RR was considered as a decrease in daily proteinuria> 30% from the initial level or less than 0.5 g in the absence of a decrease in eGFR> 25% at the time of the end of follow-up. The progression of renal dysfunction was documented with a decrease in eGFR> 25% from baseline. KO was determined as initiation of renal replacement therapy or eGFR <15 ml/min/1.73m 2 at the end of follow-up. Long-term renal survival was assessed by the Kaplan-Meier method. The median follow-up period was 18 (4; 38) months. Results: The prevalence of non-amyloid MGRS was 1.4% (n = 29) of all performed kidney biopsies (n = 2042). Clinical and demographic parameters of the group are presented in the figure 1 . Serum or/and urine paraprotein was detected in 23 patients as κ (30.4%), IgM/κ (21.7%), IgM/λ (13.1%), IgG/κ (13.1%), λ (13.1%), IgA/κ (4.3%), IgG/λ (4.3%). Morphological spectrum of non-amyloid MGRS is shown in the figure 2 . Combination of light chain deposition disease and thrombotic microangiopathy was documented in two cases. The majority of patients (82.7%) was treated with clone-specific agents. In non-IgM-associated MGRS cases bortezomib+dexamethasone (D) (n=11), melphalan+D (n=2), cyclophosphamide (CPh) +bortezomib+D (n=1), lenalidomide+D (n=1) were used. Autologous stem cell transplantation was performed in 1 case. Prednisolone+CPh based schemes were applied in 5 patients. In IgM-associated MGRS 7 patients were treated with rituximab and 1 patient with bortezomib+D due to contraindication to anti-CD20 agent. 8 patients were missed from the follow-up. HR and RR were achieved in 76.2% and 62% of the treated patients, respectively (Figure 3 ). The five-year cumulative renal survival was 44% in the non-amyloid MGRS group and did not significantly differ from renal AL-amyloidosis group when compared (Figure 4 ). Conclusion: Non-amyloid type of MGRS is a clinically and morphologically diverse entity characterized by a poor renal prognosis, especially in the absence of clone-specific therapy. Treatment of MGRS should be carried out in a timely manner with the participation of a hematologist and nephrologist in order to prevent loss of kidney function and increase life expectancy.